Constructing Layered/Tunnel Biphasic Structure via Trace W-Substitution in Tunnel-Type Cathode for Elevating Sodium Ion Storage - Wenjing Shi; Hengxiang Li; Zihan Wang; Lingyang Liu; Yixin Feng; Rui Qiao; Ding Zhang; Haibo Li; Zhaoyang Wang; Pengfang Zhang (Molecules)
Tunnel-type Na0.44MnO2 is extensively regarded as an appealing cathode for sodium-ion batteries due to its cost-effectiveness and excellent cycling performance. However, low theoretical capacity, resulting from insufficient Na+ storage sites, hinders its practical application. Herein, the strategy of constructing a tunnel-phase-dominated layered/tunnel biphasic compound was proposed via trace W-substitution and the co-precipitation method. Experimental analysis reveals that W-introduction can effectively redistribute electronic configuration, induce tunnel-to-layered structure evolution, accelerate Na+ (de)intercalation kinetics, and enhance structural stability. The optimized layered/tunnel Na0.44Mn0.99W0.01O2 cathode integrates the superiorities of the layered and tunnel structures, delivering a high capacity of 153.1 mAh g−1 at 0.1 C and outstanding cycle life, with 71% capacity retention over 600 cycles at 5 C. Significantly, the full cell assembled with the Na0.44Mn0.99W0.01O2 cathode and a commercial hard carbon anode exhibits a competitive energy density of 183.2 Wh kg−1, along with a remarkable capacity retention of 75.5% over 200 cycles at 1 C. This work not only highlights the superior sodium storage performance of biphasic composites owing to the synergistic effects between layered and tunnel structures, but also unveils new possibilities for constructing high-performance hybrid cathodes that predominantly consist of the tunnel phase using a suitable design strategy.